Profile Analysis and Lifestyle of people with foot pathologies - López López, Daniel; López López, Luis; Alonso Tajes, Francisco; García Mira, Ricardo (Revista Internacional de Ciencias Podológicas, 2010)
Foot ailments are among the most common or our health problems. Although some can be traced to heredity, many stem from the cumulative impact of a lifetime of abuse and neglect, as well as non-appropiate behavior habits. The analysis of lifestyles characterizing the everyday life, together with the need to establish a profile of patients attending who visit a podologist, allow us to consider the importance of assessing the foot and converting this assessment in an indicator of the general state of health of a patient. Diseases that affect the feet can be of various kinds: joint, muscle, skeletal, orthopedic, metabolic, vascular, neuropathic, or skin, and all of then are relevant for the life and for maintaining our independence, is a key aspect.In this article, results of a quantitative study carried out with 200 patients of both genders, without restrictions of age who attend a podiatry clinic, are described. For collecting data, a questionnaire ad hoc was designed. It allowed to obtain accurate information about the profile of the patient, in general, and of the speific characteristics of that profile: socio-demographical, behavior linked to lifestyles, everyday habits, subjective relevance, preventing behaviors, as well as perception and motivation.Results focus in the relevance of social perception studies of podologist and foot deseases, as well as in the need of incorporating subjective information in the analysis of the foot problems, and those behaviours involving risks for foot health of the human beings. This perspective contribute to the deeper analysis of the social meaning of podology, and the best way to deal with the increasing number of diseases that can reduce the quality of life, due the persistence of some behaviours, potentially generating risk of foot diseases.
Keywords: Health; Lifestyle; Foot disorders; Wellbeing; Life quality